From tiny microalgae to huge biorefineries - Gouveia, Luisa (2014)
Microalgae are an emerging research field due to their high potential as a source of several biofuels in addition to the fact that they have a high-nutritional value and contain compounds that have health benefits. They are also highly used for water stream bioremediation and carbon dioxide mitigation. Therefore, the tiny microalgae could lead to a huge source of compounds and products, giving a good example of a real biorefinery approach. This work shows and presents examples of experimental microalgae-based biorefineries grown in an autotrophic mode at a laboratory scale.